The Effect of Chat Generative Pre-Trained Transformer and Storytelling on Communication Response in Lampung Geh's Video Content - Wawan Hernawan; Hasan Basri; Renanda Rizki Aryshena (Journal of World Science, 2024)
The development of digital technology has brought significant changes in how content is consumed and delivered to audiences. In this era, technologies such as Chat-GPTand Storytelling techniques are increasingly popular in video content creation, including on platforms such as Lampung Geh. This study aims to determine the effect of Chat Generative Pre-Trained Transformer and Storytelling on Communication Response on Lampung Geh Video Content. The method used in this research is quantitative. This study involved 300 respondents using an online questionnaire consisting of 14 questions. The data were analyzed using validity, reliability, and classical assumption tests such as normality, multicollinearity, and heteroscedasticity tests. The results showed that the use of Chat Generative Pre-Trained Transformer and Storytelling together significantly influenced the Communication Response of Lampung Geh audience. Individually, both variables X1 and X2 each influence variable Y. The coefficient of determination shows that Chat Generative Pre-Trained Transformer and Storytelling can explain 58.4% of the variability in Communication Response. In comparison, other factors influence the remaining 41.6%. This research provides valuable insight into the relationship between using artificial intelligence chat-GPT and Storytelling with Lampung Geh's audience's communication response. The research has implications for providing valuable insights into the relationship between the use of Artificial Intelligence Chat-GPT and Storytelling with the Communication Response of the Lampung Geh audience. The implication is that the use of AI technology and effective storytelling techniques can increase audience interaction and engagement so that it can be an essential strategy for creating more exciting and influential video content.